EFFECTIVENESS TEST OF MIMBA EXTRACT (Azadirachta indica A. Juss.) AGAINST PARASITE ON TILAPIA FISH SEED (Oreochromis niloticus) AT FISH SEED OFFICE, PENEBEL, TABANAN REGENCY, BALI PROVINCE - Anak Agung Sagung Risa Andriani; Sang Ayu Made Putri Suryani; I Wayan Arya (UPT Penerbitan Universitas Jember, 2017)
Mimba leaf (Azadirachta indica A. juss.) is good for sanitation and disease control at the fishseed. Mimba leaf contains many compounds that can be an antiseptic, antivirus, antibacterialand antiparasite. The purpose of this research is to know kind of ectoparasite that attack CarpFish seed in Fish Seed Office at Penebel and to know how much effective doses from Mimbaleaf extract to wipe out parasite in Carp Fish seed. Disease countermeasures in Carp fish seedhave done by using chemical especially antibiotic. Continual using chemical material willcause a negative impact on the fish, environment and also consumer. Using Mimba leaf as anorganic disease control is a good choice. The result research by using Mimba leaf extract asantiparasite with different doses show deference effectiveness level. 15 ppm dose is the mosteffective to wipe out the parasite in Tilapia Fish where after soaked with mimba leaf extractseen that kind of ectoparasite that susceptible with mimba leaf extract are Tricodina sp,Argulus sp, sp Gyrodactylus, Dactylogyrus sp, Myxobolus sp, sp Henneguya, and Oodinium spp.